Synthesis and Straightforward Quantification Methods of Imino Nitroxide-Based Hexaradical Architecture on a Cyclotriphosphazene Scaffold - Fidan, Ismail; Onal, Emel; Yerli, Yusuf; Luneau, Dominique; Ahsen, Vefa; Hirel, Catherine (AMER CHEMICAL SOC, 2016)
The synthesis of a homogeneous neutral hexaradical architecture consisting of six imino nitroxide radical moieties covalently bonded on a cydotriphosphazene scaffold was reported. The synthesis of hexaradical imino nitroxide compounds follows the Ullman procedure involving the condensation of 2,3-bis-(hydroxylamino)-2,3-dimethylbutane with hexa-(4-formylphenoxy)-cydotriphosphazene (3) followed by oxidation of the condensation product hexa-[4-(1-hydroxy-4,4,5,5-tetramethyl-2-imidazoline-2-yl)-phenoxy]cydotriphosphazene (2) by NaIO4. Characterization of hexaradical was performed by X-ray and SQUID in solid state and by EPR, absorption spectroscopy, and electrochemistry in solution. CV of 1 shows an oxidation peak at 1.184 V (vs SCE) and a reduction peak at -0.883 V, both characteristics of the presence of phenyl imino nitroxide (7) moieties, suggesting that the contribution of the cydotriphosphazene core is negligible. Attention was particularly focused on developing methods, UV-vis spectroscopy and square-wave voltammetry, to quantify the number of radicals in a way to confirm easily and rapidly the polyradicals' structure.
Keywords: NITRONYL NITROXIDES; FREE-RADICALS; MODEL; PHTHALOCYANINE; DENDRIMERS; Chemistry